TREATMENT OF COMMON DENTAL INJURIES DURING SPORT ACTIVITIES -CASE REPORT - Mijoska, Aneta; Jovanovski, Sasho (Journal of Morphological Sciences, 2021)
Several different sports like karate, handball, basketball, or some other sport activities like riding a bike or roller skaters often cause dental trauma in young patients. Accidental falls, impacts and hits play major role in these injures, sometimes even with serious health impact. Soft tissue trauma presents a high percentage of injures, but 40% are dental traumas, and upper maxillary incisors are most affected.Fractured or lost upper first maxillary incisor demands immediate restoration. Prosthetic solutions for different sport facial and dental traumas are crowns, removable partial dentures or implants. Managing the pain fast with different treatment choices like extraction of the tooth, endodontic treatments and early temporary prosthetic therapy protocols are showing good results. Individual approach for every type of trauma is needed, and most of the patients are accepting the suggested treatment plan. Restored teeth show good aesthetic and function solutions, too. Choosing the best therapy treatments in these patients is very important, because dental trauma can also cause some psychological and social problems. Immediate treatment is necessary, and proper restoring often demands a team effort . Keywords: sport dental injuries, fracture, mouthguards. https://doi.org/10.55302/JMS2143027m